Development of Digital Education Based on Starlink Satellite Technology to Improve Students' Access to Online Learning In Blank Spot Areas - Ardi Rahmawan; Puji Laila Ramadhan; Syaiful Islami; Nestika Ratum (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study was motivated by limited internet access in blank spot areas, which hinders online learning, reduces student participation, and affects learning outcomes, digital skills, and learning motivation. The purpose of this study was to analyze the implementation of Starlink satellite technology in improving students’ access to online learning in blank spot areas. This research employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, observations, documentation, questionnaires, and pre-test and post-test assessments, then analyzed using a mixed methods approach. The results showed that Starlink implementation increased stable signal availability from 32% to 92%, internet access from 28% to 88%, and online learning smoothness from 35% to 90%. Students’ average scores increased from 62 to 84, learning mastery from 45% to 85%, digital skills from 50% to 83%, and learning motivation from 55% to 88%. Therefore, Starlink is effective as an alternative solution to reduce the gap in online education access in blank spot areas.